2018
DOI: 10.1007/jhep11(2018)197
|View full text |Cite
|
Sign up to set email alerts
|

$$ \mathcal{N} $$ = 1 dualities in 2+1 dimensions

Abstract: We consider minimally supersymmetric QCD in 2+1 dimensions, with Chern-Simons and superpotential interactions. We propose an infrared SU(N) ↔ U(k) duality involving gauge-singlet fields on one of the two sides. It shares qualitative features both with 3d bosonization and with 4d Seiberg duality. We provide a few consistency checks of the proposal, mapping the structure of vacua and performing perturbative computations in the ε-expansion.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 57 publications
3
76
0
Order By: Relevance
“…In [1] we showed that the merging pattern of the 4 bosonic and 4 bosonic fixed points suggested by large N f argument is consistent with various boson ↔ fermion dualities conjectured to hold when the number of flavors is N f =2 [1,21,22] (see also [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] for recent progress in 2+1d dualities). This scenario is also consistent with lattice simulations, that at small N f [43][44][45][46][47] suggest second order or weakly first order phase transition, and with numerical bootstrap results relevant for N f =2 [48][49][50][51].…”
Section: Jhep05(2019)214supporting
confidence: 69%
See 1 more Smart Citation
“…In [1] we showed that the merging pattern of the 4 bosonic and 4 bosonic fixed points suggested by large N f argument is consistent with various boson ↔ fermion dualities conjectured to hold when the number of flavors is N f =2 [1,21,22] (see also [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] for recent progress in 2+1d dualities). This scenario is also consistent with lattice simulations, that at small N f [43][44][45][46][47] suggest second order or weakly first order phase transition, and with numerical bootstrap results relevant for N f =2 [48][49][50][51].…”
Section: Jhep05(2019)214supporting
confidence: 69%
“…For this purpose first we notice that the action (4.24) without the first term is the N = 1 supersymmetric O(N ) sigma model [89]. The large N f scaling dimensions of the field σ and of the bilinear adjoint operator for this model have been computed in [89] (see [39] for a finite-N f study in the 4 − expansion): Finally, for the completeness, we compute the scaling dimensions of the scalar mesonic operators in N = 2 SQED, which at leading order have dimension 2, but are not protected. One such operator is the quartic adjoint-2: |Φ| 4 adj−2 , to calculate its scaling dimension one uses graphs in the tables 14, 16.…”
Section: Jhep05(2019)214mentioning
confidence: 99%
“…However, the improved understanding that we now have of the dynamics of N = 1 three-dimensional CS-matter theories (see e.g. [12,[16][17][18][49][50][51][52]), together with a few more facts which were not fully appreciated previously, let us reconsider this problem and provide a more complete and satisfactory picture, in the regime F < N . For instance, in Table 2 we list all BPS domain walls of SU (N ) SQCD for N ≤ 5.…”
Section: Introduction and Summary Of Resultsmentioning
confidence: 99%
“…As before, it is convenient to rescale the meson field M and the spatial coordinate x (as well as to possibly shift the phase of the central charge) 20 as 17) in order to obtain dimensionless differential equations,…”
Section: Symmetry Breaking Wallsmentioning
confidence: 99%
“…The authors of [22] proposed the following duality (and related SU −U and U −U dualities) for the case N f = 1:…”
Section: Discussion Of Dualities and Exact Moduli Spacesmentioning
confidence: 99%